The Free-Tuition Movement - de Gayardon, Ariane; Bernasconi, Andrés (International Higher Education, 2020)
This article gives an insight into the free-tuition movement observed globally. It analyses the forces that led to the adoption of free-tuition policies and questions their sustainability in light of recent events in countries that adopted such policies.